Equine Dermatophytosis caused by Nannizzia gypsea - Molecular Diagnosis by qPCR - Andréia Spanamberg; Angélica Bundchen; Beatriz Fuentes; Laerte Ferreiro (Acta Scientiae Veterinariae, 2024)
Background: Dermatophytes, fungi of universal distribution, invade semi or fully keratinized structures, such as skin, fur/hair and nails. In companion animals (cats, dogs, or small mammals like rabbits, guinea pigs, and chinchillas) as well as in large animals (mainly in horses and cattle). Frequently are responsible for skin diseases including alopecia and crusts. This work reported a case of equine ringworm due to Nannizzia gypsea (Microsporum gypseum) detected from the clinical sample by SYBR-Green real-time PCR. The strategy was based on the DNA extraction directly from the infected hair followed by real-time PCR and melting-point analysis. Case: A 2-year-old horse was referred to the Veterinary Clinic Hospital, Federal University of Rio Grande do Sul (HCV-UFRGS), Porto Alegre, Brazil, presenting circular areas of alopecia and lesions with dry aspect and thin powdery scales and hairs broken at their base mainly on head and neck. No previous antifungal treatment was carried out. The sample was obtained by plucking the hair with forceps and scales from the peripheral area of the lesions. For mycological diagnosis, hair specimen was clarified and examined microscopically using 10% potassium hydroxide (KOH) for the visualization of arthroconidia (ectothrix type). The infected hair was plated onto Mycosel TM Agar and Mycosel Agar with nicotinic acid requirement, incubated at 25-30°C for 10-15 days. Microscopic features (macroconidia) and colony characteristics (colors and texture) were conducted for the differentiation of the species within the genus Microsporum. In addition, real-time PCR was applied for direct analysis of the fungal DNA obtained from the hair sample. Qiagen DNeasy® plant mini DNA extraction kit protocol was used to extract DNA from the hair sample according to the manufacturer's instructions. A real-time PCR was performed using the pan-dermatophyte primers for detecting a DNA fragment encoding chitin synthase 1 using SYBR Green PCR Mix. The melting curve data were obtained by continuous fluorescence acquisition from 60 to 95°C with a ramp rate of 0.3C. Microscopic examination of hair sample was negative. The culture was positive and dermatophyte present in the hair sample was confirmed as Nannizzia gypsea (M. gypseum) following the amplification of CHS1 gene. The hair sample melted at 83.78°C, showing that the isolated clinical curve was distinct from the control (M. canis) melted at 85.3°C. Discussion: Animals can be infected by a variety of dermatophytes. Nannizzia gypsea (Microsporum gypseum) is a geophilic keratinophilic fungus with a worldwide distribution which may cause infections in animals and humans, particularly children and rural workers during warm humid weather. Usually produces a single inflammatory skin or scalp lesion. The dermatophytic infection in horses is generally follicular and the most common clinical sign is one or many circular areas of alopecia with variable erythema, scaling and crusting. Is extremely important the culture of samples from skin lesions, because many agents may be involved and, frequently KHO test is negative. Conventional methods (direct exam and fungal culture) lacks the ability to make an early and specific diagnosis. The qPCR assay introduced in this study allows the specific detection of relevant dermatophytes in veterinary medicine in a short time. In the case reported here, dermatophytosis due Nannizzia gypsea (Microsporum gypseum) in a horse was confirmed based on mycological diagnosis and SYBR-Green real-time PCR. Keywords: horse, ringworm, zoonosis, Microsporum gypseum, geophilic, real-time PCR.